Penerapan Supervisi Akademik dalam Meningkatkan Pendidikan di SDS Mitra Sejati - Maysarah, Nursiti; Muthmainnah, Fadhillah; Simanjuntak, Sri Nurjamilah; Rambe, Awaluddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The standard of education in a nation has an influence on its progress. Through the interaction between students, educators, and learning resources, education is a teaching and learning activity. The rest is influenced by society and the surrounding environment, but these three main factors greatly affect the quality of education. It is hoped that every educational staff member understands the importance of educational supervision in the learning process to support the improvement of the quality of education, so that every educator and educational staff member can effectively carry out their supervision responsibilities in accordance with their rights and authority. Education is expected to be able to produce a next generation of the nation that has competitive academic and non-academic potential. Educational supervision helps to restore and improve the education system in Indonesia. However, there are still some problems in the implementation of educational supervision, such as supervisors who are unable to carry out their responsibilities to the best of their ability, lack of awareness of the importance of educational supervision in realizing quality education, and lack of educational supervision infrastructure.